ANALISIS KAPASITAS BUNDARAN (STUDI KASUS BUNDARAN MANDONGA KOTA KENDARI) - Nuhun, Ridwansyah (Universitas Halu Oleo, 2013)
AbstractMandonga roundabout is one of the important roundabout in Kendari, which serve the traffic flow from different directions, namely the current traffic flow coming from Sam Ratulangi street, Drs. H. Abd. Silondae, and R Soeprapto street. The high volume of traffic that passes through the roundabout causing quite chaotic meetings vehicles from different directions, either from the direction of Sam Ratulangi street. The high volume of traffic that passes through the roundabout causing quite chaotic meetings vehicles from, Drs. H. Abd. Silondae street. The high volume of traffic that passes through the roundabout causing quite chaotic meetings vehicles from, and R. Soeprapto street. The high volume of traffic that passes through the roundabout causing quite chaotic meetings vehicles from. Based on these problems, the authors will try to analyze the performance of the Mandonga roundabout. Hopefully, by the research performance of the roundabout at the roundabout Mandonga constituent can find solutions to conflicts that occur in the flow of the traffic roundabout. The purpose of this research was conducted to analyze the performance levels Mandonga roundabout, on the present and future.Performance analysis method using the method Indonesian Highway Capacity Manual 1997 (MKJI). The results showed that the largest flows occur at the ceiling of 09:00 to 10:00 hours WITA by the degree of saturation ( DS ) is the arm ( AB ) 0.294 , ( BC ) .233 , ( CA ) 0.213 . Roundabout traffic delays mean = 1.6 sec / pcu, Delay roundabout = 5.147 sec / smp. Opportunities Queue roundabout at least 2 % and a maximum of 7 %. From the analysis of the Roundabout Mandonga forecasting traffic flow is only able to serve up to 2021 with the highest DS 0.817, indicating that Roundabout Mandonga require a traffic management , or geometric changes.Recommendations for solving problems using geometric changes are backed and wide meperkecil islands side on each arm. And the results obtained that the performance of the Roundabout Mandonga decreased significantly. Namely the braid ( AB ) value of 0.642 DS , ( BC ) value of 0.522 DS , ( CA ) with the degree of saturation ( DS ) 0.582 . Roundabout traffic delays mean = 2.94 sec / pcu, Delay roundabout = 6.94 sec / smp, Opportunities Queue roundabout at least 6 % and a maximum of 23 %.?Keywords: Roundabout, Performance, Prediction?AbstrakBundaran Mandonga merupakan salah satu bundaran penting di Kota Kendari, yang melayani arus lalulintas dari berbagai arah, yaitu arus arus lalulintas yang berasal dari Jl. Sam Ratulangi, Jl. Drs. H. Abd. Silondae, dan Jl. R Soeprapto. Tingginya volume lalulintas yang melewati bundaran ini menyebabkan terjadinya pertemuan kendaraan yang cukup semrawut dari berbagai arah jalan, baik dari arah Jl. Sam Ratulangi, Jl. Drs. H. Abd. Silondae, dan Jl. R Soeprapto.? Berdasarkan permasalahan tersebut, maka penyusun mencoba menganalisis kinerja bundaran Mandonga tersebut.? Tujuan dari penelitian ini dilakukan untuk menganalisis tingkat kinerja bundaran Mandonga, pada kondisi sekarang dan yang akan datang.Metode analisis kinerja dengan menggunakan metoda Manual Kapasitas Jalan Indonesia 1997 (MKJI). Hasil penelitian menunjukkan bahwa arus terbesar terjadi pada pagu hari jam 09.00-10.00 WITA dengan nilai Derajat Kejenuhan (DS) yaitu pada lengan (AB) 0,294, (BC) 0,233, (CA) 0,213. Tundaan lalulintas bundaran rata-rata = 1,6 det/smp, Tundaan bundaran = 5,147 det/smp. Peluang Antrian bundaran minimal 2% dan maksimal 7%. Dari hasil analisa peramalan Bundaran Mandonga hanya mampu melayani arus lalulintas sampai tahun 2021 dengan DS tertinggi 0,817, Hal ini mengindikasikan bahwa Bundaran Mandonga memerlukan suatu manajemen lalulintas, ataupun perubahan geometrik.?Rekomendasi pemecahan masalah dengan menggunakan melakukan perubahan geometrik yaitu memundurkan dan meperkecil lebar sisi pulau-pulau pada tiap lengan. Dan hasil yang diperoleh bahwa kinerja Bundaran Mandonga menurun signifikan. Yaitu pada jalinan (AB) nilai DS 0,642, (BC) nilai DS 0,522, (CA) dengan nilai derajat kejenuhan (DS) 0,582. Tundaan lalulintas bundaran rata-rata = 2,94 det/smp, Tundaan bundaran = 6,94 det/smp. Peluang Antrian bundaran minimal 6% dan maksimal 23%.?Kata Kunci: ?Bundaran, Kinerja, Prediksi